Italian verb to noun conversion: the case of nouns in –a deriving from verbs of the 2nd and 3rd conjugation - Marzo, Daniela (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
The formation and structure of the following Italian deverbal nouns is an open question in Italian word-formation research: (1a) cammino, (1b) ritegno, (1c) riparto, (2a) sosta, (2b) classifica, (3a) tema, (3b) basta, (3c) perquisa. While instances such as in (1) and (2) have, depending on the theoretical background, been analysed either as root conversion (cf. (1)) and conversion of the infinitival stem (cf. (2)) or as suffixation (cf. (1) and (2)), the spectrum of accounts for the instances in (3) includes, in addition, root conversion with analogical gender assignment (cf. (3a) and (3b)) as well as analogical backformation (cf. (3c)). In the present contribution it is shown that the current conversion approaches as well as the suffixation approach are insufficient to explain the formation and structure of the nouns in (1) to (3). While the suffixation account is ruled out mainly for semantic and distributional reasons, it is shown thatthe existing conversionaccounts are, in principle, more plausible to account for the nouns in (1) and (2). However, as for the analogy-based conversion approaches, it is shown that only (3c) is a proper analogy-driven formation. In contrast, type (3b) will be shown to be an instance of root conversion remodelled by blocking. Moreover, in order to explain the formation and structure of the noun type instantiated by (3a), an additional type of conversion has to be distinguished: (3a) is shown – by the help of data from Old Italian– to be a synchronic remnant of an Old Italian conversion type: conversion of stem 2 of the Italian verbal stem space (terminology from Giraudo, Montermini&Pirrelli 2009), i.e. the stem on which also some Italian inflectional forms, as e.g. some of the present subjunctive forms are constructed.